The Use of Bacteriocin Powder from Bacteria Lactobacillus plantarum as Biopreservative Agent of Cassava Getuk - Khilda Azka Krisnani, Fransisca Maria; Purwijantiningsih, L.M. Ekawati; Pranata, Fransiskus Sinung (Journal of Food and Life Sciences, 2020)
Getuk is an Indonesian traditional food made from cassava. Getuk has short shelf life, which is 12-15 hours caused by the high water content in getuk that is make getuk easily contaminated by microbes. Biopreservation is a safe solution to overcome this problem, one of which is by using bacteriocin. Bacteriocin is safe to use as a biopreservative because it is not toxic and can be digested by the protease enzyme so it will not affect the microbiota in the intestine. Bacteriocin used in this study is bacteriocin produced by Lactobacillus plantarum because it is a safe microbial and included in GRAS (Generally Recognized as Safe) and has broad spectrum properties, which can kill gram-positive, gram-negative, and pathogenic bacteria. This research will discuss further about the ability of bacteriocin from Lactobacillus plantarum as a biopreservative agent in getuk. Bacteriocin from Lactobacillus plantarum will be microencapsulated using spray drying before adding to getuk. The treatments taken are variations in the addition of bacteriocin to getuk and variations in storage time. The variation of bacteriocin addition in getuk is 0% (control), 2,5%, 5%, and 7,5%, the variation of getuk storage time is 0-3 days. Cassava getuk will be tested physically, chemically, and microbiologically during the storage time. The results obtained in this study are the addition of 7,5% bacteriocin powder can increase getuk shelf life for 1 day. On storage day 1, the result of microbe in getuk is still within the national standard safe limits and getuk does not smell sour and there is no yeast that grows on getuk.